(untitled) (Zaporizhzhia Historical Review, 2021)
The article touches upon the causes of the revolt of the right parties in town Rivne on April 29, 1919. Special attention is paid to the military and political situation in Ukrainian People’s Republic of the time, which was conditioned by the climax of governmental crisis and collisions between the Ukrainian right and left parties.